Efficiency Investigation of a Four-Segment Permanent Magnet Flux Reversal Motor Design - Muhammad Hakim Zam Telani; Mahyuzie Jenal (Evolution in Electrical and Electronic Engineering, 2025)
The paper focuses on the segmented stator Flux Reversal Motor (FRM). It lists some critical optimization difficulties which include flux leakage and cogging torque, with an objective of improving the efficiency through use of Finite Element Analysis (FEA). Building on what is already known regarding the operation of flux reversal and permanent magnet machines the paper examines new design features such as segmental stators to said matters of faults and torque. These insights provide a framework as a basis for designing the proposed FRM. A scientific procedure was used for designing and simulating the motor with the help of JMAG Designer 18.1. These were followed by several basic parameters such as parameter specification, geometry modification, material determination, and other performance checks. Closely related with pm synchronous motors, the analyses of the relationship between torque, flux linkage, and efficiency to set up design parameters. Using performance evaluation, the design of the 12-stator-slot, 16-pole SSFRM yielded a peak torque of 43.05 Nm with a power output of 22.24 kW. Although the design revealed stable flux interaction and ability to handle faults, the design absorbed a very high amount of copper losses (39.68 kW) thereby limiting its efficiency to 50.8 %. This points to the problem of optimisation, now, especially with the focus on the magnetic and material quality. In turn, the overall potential of the SSFRM for energy efficient applications is presented, with the segmental stator appearance giving it significant possibilities. However, increasing efficiency and minimising losses has to be achieved, in order to make its real-life application and commercial utilization.